Semi-distributed hydrological modeling in the Titicaca hydrographic region: case study of the Ramis river basin, Peru - Lujano Laura, Efrain (2016)
The present research was held in the basin of the river Ramis, located in the hydrographic region of Titicaca, Peru, with the objective of calibrating and validating the Sacramento hydrological model (SAC-SMA) from a semi-distributed approach. The hydrometeorological information used for rainfall, temperature and ﬂow, correspond to a series of records 2005 - 2016. The methodology of spatial interpolation of meteorological data in the virtual station was estimated using the Shepard procedure and potential evapotranspiration by the model Turc, these methodologies are incorporated in the RSMINERVE platform and are automated estimates. The calibration and validation phase of the model was performed randomly with 70% and 30% of the total data respectively. The statistical evaluation of efﬁciency and error were measured by the Nash coefﬁcient, Nash coefﬁcient for logarithm values and root mean square error. The results are satisfactory and it is stated that the outputs of the hydrological model adequately represent the ﬂows of avenue and drought, constituting as an alternative for the strengthening of the hydrological forecast at the daily time step of the river Ramis.